2021
DOI: 10.1177/09544062211027209
|View full text |Cite
|
Sign up to set email alerts
|

Influence of inlet swirl on pattern factor and pressure loss in an aero engine combustor

Abstract: The effect of compressor exit swirl angle (θsw) at the intake of an aero engine combustor on the exit temperature non-uniformity (pattern factor) and combustor total pressure loss is investigated. Experiments are conducted in the engine test rig, measuring the gas temperature and pressure at the inlet and exit planes of the combustor. These parameters are measured at distinct locations along the circumferential and radial directions in the engine test facility. Simulations are carried out using RANS based turb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Different types of combustion chambers have been developed in the past century and different fuels are used there. In aero-engine or gas turbine combustor design, complete combustion, 1-3 low total pressure loss, 4 stability, 5,6 freedom from flash back and flame out, 7,8 relightabality, 9,10 occupying a small space, and no hot spots [11][12][13] are desired, and many researches have been performed on these areas to have better designs.…”
Section: Introductionmentioning
confidence: 99%
“…Different types of combustion chambers have been developed in the past century and different fuels are used there. In aero-engine or gas turbine combustor design, complete combustion, 1-3 low total pressure loss, 4 stability, 5,6 freedom from flash back and flame out, 7,8 relightabality, 9,10 occupying a small space, and no hot spots [11][12][13] are desired, and many researches have been performed on these areas to have better designs.…”
Section: Introductionmentioning
confidence: 99%
“…The study's findings showed that 75° was the best-optimized design (in terms of turbulent kinetic energy) for achieve superior swirl [16]. Furthermore, this research provides insight into how to develop novel methods for enhancing mixing by increasing turbulent kinetic energy [16,17].…”
Section: Introductionmentioning
confidence: 99%